Clinical potential of photodynamic diagnosis and therapy of tracheobronchial malignancies in the visible and infrared spectral ranges. Issue 1 (9th March 2020) - Papayan, Garry; Goncharov, Sergey; Kazakov, Nikita; Strui, Andrey; Akopov, Andrey
Abstract: This article describes a video endoscopy system intended for fluorescence‐based imaging of the tracheobronchial tree in the visible (VIS) and near‐infrared (NIR) regions of the spectrum. This system helps acquire both fluorescence images (VIS/NIR) and a white‐light image of the same area and has been developed on the basis of a standard bronchofiberscope with several diode lasers used as the light sources to excite Vis and NIR, the white‐light source, and photodynamic irradiation. A multimodal video system forms images and gives the possibility to perform targeted photodynamic therapy and control the dose of light irradiation through assessing the degree of photobleaching.The system capability is illustrated through clinical examples. The paper describes the procedure for photodynamic theranostics with chlorin e6 in patients with central lung cancer. The possibility of additional accurate localization of tumor lesions and their borders with NIR imaging is shown; to acquire a NIR image, a common dose of indocyanine green (ICG) used in angiography was administered to patients during the examination. It is also demonstrated that the same lesions can be identified using a combination of two dyes: chlorin e6 + ICG. Abstract : This article describes a video endoscopy system intended for fluorescence‐based imaging of the tracheobronchial tree in the visible (VIS) and near‐infrared (NIR) regions of the spectrum. This system helps acquire both fluorescence images (VIS/NIR) and a white‐light image of the same area and has been developed on the basis of a standard bronchofiberscope with several diode lasers used as the light sources to excite Vis and NIR fluorescence, the white‐light source, and photodynamic irradiation.